NEW MODIFIED EQUATION OF LONGSHORE CURRENT VELOCITY AT THE BREAKING POINT (FOR MIXED AND GRAVEL BEACHES) - Christos Antoniadis (JOURNAL OF COASTAL DEVELOPMENT, 2013)
Wave breaking is the dominant process in the dynamics of nearshore water movements resulting in sediment transport. The transformation of the subsequent particle motion from irrotational to rotational motion generates vorticity and turbulence and this affects the sediment transport. An improved understanding of the location of the breaker point and characteristics of the wave under these changing parameters is essential to our understanding of short and long-term morphological beach development. This paper reports a series of 3-dimensional physical model tests to measure longshore current data, generated by oblique wave attack, along gravel and mixed beaches with a uniform slope and a trench. The studies described in this paper aim to improve the Longuet-Higgins’s formulae which predicted the longshore current velocity at the breaking point.